Pieriestrojka znaczy smuta? O mentalno-społecznym kontekście sposobu pojmowania przez Rosjan gorbaczowowskich przemian - Broda, Marian (Eastern Review, 2016)
If in the West perestroika and its initiator, Mikhail Gorbachev evoke, almost involuntarily, mostly warm and positive connotations, Russians’ attitude and assessment towards them are, more and more explicitly and unequivocally, strongly negative. Interestingly and symptomatically, in the consciousness of the millions of Russians, the governance of both Gorbachev and Yeltsin – competing leaders who were programmatically in opposition – is regarded in the category of Smuta (the Time of Troubles), meaning, recurring in the Russian history, periods of defiance, feud, disarray, chaos, helplessness and decay. Analyzing and explaining the above, one should remember that the subjective power making history has for centuries been identified with the central national authority seeing in its existence, self-rule, might and efficiency not only the guarantee, but also the basis for existence and creation of the social order, or even the existence of the state itself in the, supposedly, invariably hostile world towards Russia. The presumptions of the similar – consolidated, disseminated, and reproduced for ages – way of experience, conceptualization, assessment and Russians’ problematization of the social reality do not have only a mental-cultural character, but their basis and correlates-counterparts also lie in the institutional-social sphere. Recurring throughout the Russian history periods of the weakening of power – together with the democratization attempts of (self-)limiting its authority – strengthen the processes of mental and social disintegration, create attitudes of life helplessness, destroy the sense of common value, identity and sense of existence. If so, Russian experience of the reformatory-democratic periods in their country’s history in general, and Gorbachev’s perestroika in particular, become something non-coincidental, even self-comprehensive, in the categories of, needing overcoming, the Russian Smuta. Not the first and – probably – not the last.